Methodology for Teaching the Topic "Points and Their Displays on Drawings" - Astanov T.M (Genius Publishing Group, 2023)
This article presents the methodology for teaching the topic "points and their manifestations in drawings".
Keywords: Point formation; projection plane; projection axes; drawing reading rule